Communication Pattern and Participation of Custom Village Community in Implementing Tri Hita Karana for Local Custom Conservation at Tourism Destination (Ethnographic Study at Tourism Destination of Peliatan Ubud Custom Village in Gianyar Bali) - sukertha, agus ardi (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Abstract. Research attempts to examine the information about Communication Pattern and Participation of Custom Village Community in Implementing Tri Hita Karana for Local Custom Conservation at Peliatan Ubud Custom Village. Research uses constructivist paradigm with ethnographic method. Main informant is custom leader. Snowball method is used to determine informants until valid information is obtained. Research finds that communication pattern of the community at Peliatan Ubud Custom Village is based on principles of utility, collectiveness and kinship, justice and apportionment, congeniality and harmony. All these principles are reflecting the implementation of Tri Hita Karana. The participation of the community at Peliatan Ubud Custom Village in implementing Tri Hita Karana is shown by conserving their local culture.